REASONABLE PRICE INDICATORS IN COLLECTION OF BPHTB SALE AND PURCHASE BY BAPENDA MALANG CITY - Aulia Faza Regista; Muktiono; Supriyadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The purpose of this research is to analyze and describe the indicators used by Bappenda in determining the fair transaction price for buying and selling land in Malang City in collecting BPHTB. This type of research is a socio-legal research with a juridical-sociological approach. This research was conducted at the Malang City Regional Revenue Agency. The results of the analysis show that based on the results of interviews with Bapenda, it states that a fair transaction price has the same meaning in determining market value, but for buying and selling transactions, Bapenda determines it in several ways in the form of a sales price submitted by the taxpayer as the seller, the previous documents where there are similarities in certain districts or sub-districts, can also be seen by neighboring houses that are next door and around it. Of these 3 things, Bapenda takes the average to determine a fair transaction price. The use of the price contained in the Bappenda tax database is used as a measure to find out whether the stated transaction price is a reasonable transaction price. Considering that many taxpayers include the transaction price on the Sale and Purchase Deed and SSPD BPHTB which does not match the actual price to minimize the amount of BPHTB owed.